Beyond Illyria: Workers' firm in mixed oligopoly - Flavio Delbono; Diego Lanzi; Carlo Reggiani (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2022)
We rationalize several facts emerging from the recent empirical research on cooperatives owned by workers (workers' firms, WF) as: the concern of WFs for employment; the interplay between membership and workplace safeguard within WFs; the different reaction to shocks between WFs and profit-making firms. We do so by means of a new model of WFs short-run behavior in mixed duopoly. We consider an industry in which a WF competes with a profit maximizing company and we innovate with respect to the conventional Illyrian objective function. We then reconcile the literature on labor-concerned maximands in competitive markets and the one dealing with WFs in oligopolistic markets under the Illyrian maximand.
Keywords: L13; L21; P13; 330; workers firm; employment; oligopoly